Denise Austin burn fat fast [videorecording (DVD)] - Austin, Denise; Del Pozo, Cal; Hansen, Steve S. (Lions Gate Home Entertainment, 2005)
Denise Austin presents two complementary workouts: a fat-burning cardio routine and a body-sculpting routine, targeting abs, buns, and legs.